2011
DOI: 10.1352/1934-9556-49.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Health Conditions in Children With Intellectual Disability: A Systematic Literature Review

Abstract: A systematic review of the prevalence rates of chronic health conditions in populations of children with intellectual disability was provided. We identified 2,994 relevant studies by searching Medline, Cinahl, and PsycINFO databases from 1996 to 2008. We included the 31 studies that had sufficient methodological quality. The 6 most prevalent chronic health conditions in children with intellectual disability were epilepsy (22.0/100), cerebral palsy (19.8/100), any anxiety disorder (17.1/100), oppositional defia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 85 publications
5
114
1
8
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Between 30% and 50% of children and adolescents with CD are estimated to develop mental health disorders, a risk nearly 3 times that of typically developing (TD) children. 2 Behavior problems with CD are associated with increased costs of care, 9 social isolation, 17 poor academic achievement, 17 parental stress, 7 and residential treatment placement.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Between 30% and 50% of children and adolescents with CD are estimated to develop mental health disorders, a risk nearly 3 times that of typically developing (TD) children. 2 Behavior problems with CD are associated with increased costs of care, 9 social isolation, 17 poor academic achievement, 17 parental stress, 7 and residential treatment placement.…”
mentioning
confidence: 99%
“…По разным оценкам, от 14 до 39% людей с интеллек-туальной недостаточностью имеют сопутствующие психиатрические диагнозы. У многих пациентов с ум-ственной отсталостью (5,5-35%) встречается эпи-лепсия [42]. В некоторых случаях это позволяет опре-делять умственную отсталость как следствие таких заболеваний и проводить молекулярно-генетическую диагностику, например, используя имеющиеся панели для эпилепсии [43].…”
Section: клинический полиморфизм генетическая гетерогенность и диагнunclassified
“…в 2011 г. [42]. Проведен систематический обзор 31 ста-тьи, отобранной из 2994 включенных в первоначальный анализ.…”
Section: клинический полиморфизм генетическая гетерогенность и диагнunclassified
See 1 more Smart Citation
“…assuming population frequencies of 2% for DD, 43 1% for ASD, 44,45 0.85% for epilepsy (http://www.parliament.uk/briefing-papers/ sn05691.pdf), 46 and 0.72% for SCZ, 42,47 and correcting for co-morbidity rates of 10% for ASD/DD, 48 22% for epilepsy/DD, 48 8% for epilepsy/ASD, 49 4.4% for SCZ/DD, 50,51 2.4% for SCZ/ASD 52 and 2.4% for SCZ/epilepsy. 53 Importantly, Kirov et al recently reported an overall penetrance estimation of 40% (95% CI ¼ 21-72%) for 15q13.3 microdeletions in SCZ and early-onset developmental disorders, which is very close to our estimate of 44% (95% CI ¼ 29-63%) for neurodevelopmental disorders, although the authors did not specifically include the epilepsy phenotype in their calculations, and accounted instead for various congenital malformations.…”
Section: Positive Clinical Predictive Value (Life-time Risk To Develomentioning
confidence: 99%